As analogias no ensino de conteúdos conceituais de física - Silva, Leandro Londero da (2006)
The present investigation reports a study of contributions and limitations of the use of didactic activities based on analogies for the teaching of conceptual subjects of Physics in the secondary level school. Preoccupation in evaluating analogies influences in the student s learning was considered. To reach this purpose, didactics activities based on analogies were developed. Next, the familiarity of the analogies used in the activities as well as the justifications for this were analyzed through the application of a questionnaire to 157 students and 03 teachers, including one in a researcher position. They act at 2ª and 3ª grades of 4 public secondary level schools of Rio Grande do Sul 64 from Santa Maria, 44 from Candelária and 49 from Nova Palma town. Then, the didactics activities were implementing in the classes of these teachers. At this stage, productions developed by the students were used as instruments to information recording. These productions were gathered as implementations and video-recordings of two classes lasting 50 minutes each, during the school year of ten months. At the end of time, semi-structured interviews were audio-recorded with the teachers and later they were transcribed. The analyses of students answers show that they consider only the lived and visualized analogies. The justification used to the familiarization with the analogies progressed in different aspects. While some students look for lived situations and live experiences in order to justify the familiarity with the analogies, others use knowledge related to the scope of school subjects. The students not only hold knowledge and scientific information learned at school and out of it, as well as they utilize this knowledge and information to produce their answers. Through the implementations developed, it can be observed that meaning each student constructed, around a certain concept, was formed considering the amount of analogical relations that he had established, the limitations identified and the conclusions he elaborated. Thus, it is possible to infer that as the students better understand the process of learning through the use of analogies, it is possible they improve their capacity to compromise with higher levels of learning, that is, of establishing a greater number of relations, limits and of elaborating conclusions with better argumentation. In a general sense, the students observed that learning and, consequently, the improvement in the establishing of relations, identification of limitations and development of conclusions were developed in a progressive sense. This can be supported by the use of activities related to actions classified as procedural. Then, the learning of conceptual subjects through the use of Didactic Activities based on Analogies occurs via procedures. Thus, the learning of procedures occurs slowly and this was permitted throughout the development of activities. It might be inferred that none analogy based activity can be better than the other because all of them bring distinctive aspects. Therefore, it is necessary that their characteristics, familiarity with their knowledge, procedural abilities of the students and guidance of the teacher in their implementation be considered. Generally, analogies bring multiple characteristics, though some of their characteristics can be more observable than others, and some predominant ones can be enough. Commonly, the better students performance in the required activities was observed in that ones which presented the following characteristics: a) the target or analogy presented through images or physical patterns; b) analogies possible of being role played/ simulated; c) few number of related attributes and d) analogy extracted from the everyday (out the area of knowledge). In the current moment, it could be claimed that the Didactic Activities based on Analogies are presented as a possible way to the formation of concepts and to the scope of procedures. To sum up, what can be noted in this investigation is the fact that the students construct a comprehension about the concepts studied and that they are able to perform possible procedures of being analyzed using this kind of activity. That is, they are able to perform, compare, identify, argue and register through the articulation of conceptual and procedural aspects.